2006
DOI: 10.1128/aac.00449-06
|View full text |Cite
|
Sign up to set email alerts
|

New Integron-Associated Gene Cassette Encoding a Trimethoprim-Resistant DfrB-Type Dihydrofolate Reductase

Abstract: A sixth gene cassette containing a dfrB-type gene, dfrB6, was found in a dfrB6-aadA1 cassette array in class 1 integrons. This array was isolated from several multiply antibiotic-resistant Salmonella enterica serovar Infantis strains that appear to be clonally related. The DfrB6 dihydrofolate reductase conferred resistance to trimethoprim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Trimethoprim was the only exception, where only 12 of the 27 resistant isolates investigated had dfrA12 , dfrA17 or related genes. Enterobacteria carry a diverse range of acquired trimethoprim‐resistant dihydrofolate reductase genes, with the dfrA group comprising over 20 genes (Grape et al , 2005) and the dfrB group comprising six genes (Levings et al , 2006). The remaining resistant isolates may have carried any one or more of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Trimethoprim was the only exception, where only 12 of the 27 resistant isolates investigated had dfrA12 , dfrA17 or related genes. Enterobacteria carry a diverse range of acquired trimethoprim‐resistant dihydrofolate reductase genes, with the dfrA group comprising over 20 genes (Grape et al , 2005) and the dfrB group comprising six genes (Levings et al , 2006). The remaining resistant isolates may have carried any one or more of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…A dfrA1 cassette with a 90-bp duplication in the coding sequence flanked by 15-bp direct repeats was associated with reduced levels of trimethoprim resistance (AJ400733.1, 2-end) (Gibreel & Skold, 2000). The first dfrB1 cassette identified (U36276.2, 573-1057) includes a 72-bp duplication compared with the version most common in GenBank (Levings et al, 2006). A vim1 cassette, often the vim4 variant, with a 170-bp duplication that includes all but the final C of the 1L site of attC (AY152821.1, 958-2041) (Patzer et al, 2004;Scoulica et al, 2004) is found 10 times in GenBank.…”
Section: Other Cassette Variantsmentioning
confidence: 99%
“…Bacteria carrying dfrB genes have also been identified in wastewater samples (7). Over the past decade, dfrB genes have been tracked indirectly in antibiotic resistance studies through identification of integron-related elements (8)(9)(10). Therefore, the importance of dfrB genes in TMP resistance in human pathogens may be underappreciated (11,12).…”
mentioning
confidence: 99%